PT XYZ Supplier Selection Criteria Using Analytic Network Process - Wiwik Widyaningsih (Publikasi Indonesia, 2026)
Supplier selection is very important in an industry. Choosing a supplier based on the lowest price offer is no longer efficient. The mistake of choosing a supplier will be detrimental to the company because it is related to the supplier's role as a provider of raw materials and supporting materials used in the production process. The automotive manufacturing industry requires various types of materials that are directly or indirectly involved in the production process. Therefore, the support and availability of materials from suppliers is very important. The supplier selection process is a strategic step for the company to achieve optimal production performance so that it is able to compete with other companies. PT XYZ is one of the automotive manufacturing companies in Indonesia that must meet various customer requirements, including material fulfillment through an effective supplier selection process. This study uses the Analytic Network Process (ANP) method, which is a decision-making method that is able to accommodate many interdependent criteria. The problem of supplier selection is modeled in a system that takes into account the relationship of dependency and feedback. The relationship includes comparisons between elements in one group (node comparison) and comparisons between groups of elements (cluster comparison). The ANP method generates a priority weight value for each element in the decision-making structure. The results of the observation stated that the criteria used by the company are related to each other, so the right method to use is ANP (Analytic Network Process).